A most novel revenge : a mystery - Weaver, Ashley (Weaver, Ashley. Amory Ames mystery., 2016)
"Amory and Milo Ames are drawn into the investigation of a years-old murder by a salacious novelist in the English countryside in the latest installment in this "smart and sophisticated" (Library Reads) series from a bright new voice in traditional mysteries. With two murder investigations behind them and their marriage at last on steady ground, Amory and Milo plan to quietly winter in Italy. The couple find their plans derailed when Amory receives an urgent summons from her cousin Laurel to the English countryside. At Lyonsgate, the country house of Laurel's friend Redinald Lyons, Amory and Milo are surprised to discover an eccentric and distinguished group of guests have been invited, led by notorious socialite Isobel Van Allen. Isobel has returned to England after years of social exile to write a sequel to her scandalous first book, the thinly-fictionalized account of a high-society murder at the very country house the Ameses have been called to. Her second incriminating volume, she warns the house's occupants--all of whom were present when one of their companions was killed years ago--will tell everything that really happened that fateful night. But some bones are meant to stay buried, and when a desperate person turns to murder, it's up to Amory and Milo to sort through a web of scandal and lies to uncover the truth, and the identity of a killer"--